2018
DOI: 10.1159/000489958
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV Improves Vasodilatation Function by Regulating the PI3K/Akt/eNOS Signaling Pathway in Rat Aorta Endothelial Cells

Abstract: Coronary heart disease (CHD) remains a major public health burden. Endothelial-dependent coronary artery vasoreactivity is a significant indicator of vascular function. Endothelial dysfunction is characterized by decreased nitric oxide (NO) bioavailability and predicts late cardiovascular events. Astragaloside IV (AGIV) is the main active component of the herb Astragalus membranaceus. Although it shows a significant protective effect against vascular endothelial dysfunction, the mechanisms of AGIV promoting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 48 publications
1
36
0
Order By: Relevance
“…Astragaloside IV (As-IV) is a natural nonsynthetic bioactive saponin extracted from the dried root of Astragalus membranaceus [ 13 ] and was widely observed to exert anti-inflammatory and antioxidation effects in various cells and animal models [ 14 17 ]. The potent ability of As-IV to restore endothelial dysfunction has also been demonstrated [ 18 ] which is consistent with our previous reports [ 19 ]. Although there is evidence that As-IV has the potential to prevent endothelial dysfunction, the exact mechanism by which As-IV acts against endothelial dysfunction remains unclear.…”
Section: Introductionsupporting
confidence: 92%
“…Astragaloside IV (As-IV) is a natural nonsynthetic bioactive saponin extracted from the dried root of Astragalus membranaceus [ 13 ] and was widely observed to exert anti-inflammatory and antioxidation effects in various cells and animal models [ 14 17 ]. The potent ability of As-IV to restore endothelial dysfunction has also been demonstrated [ 18 ] which is consistent with our previous reports [ 19 ]. Although there is evidence that As-IV has the potential to prevent endothelial dysfunction, the exact mechanism by which As-IV acts against endothelial dysfunction remains unclear.…”
Section: Introductionsupporting
confidence: 92%
“…Our previous findings demonstrated that ASV significantly inhibited epithelial-mesenchymal transition induced by transforming growth factor-β1 during the progression of lung fibrosis (11). In addition, previous findings suggested that ASV induced vasodilation by regulating nitric oxide production in the endothelium (12) and it improvesd vascular endothelial dysfunction induced by hyperglycemia via the toll-like receptor 4/nuclear factor (NF)-κB signaling pathway (13). Although the protective effects of ASV on endothelial dysfunction have been reported, the detailed molecular mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…A recently study showed that, a Chinese herbal medicine extract (TFCC) protects against myocardial injury and enhances cellular antioxidant defense capacity by inducing the phosphorylation of Akt, which subsequently activates the Nrf2/HO-1 signaling pathway. 29) In addition, two studies showed that AS-IV has protective effects on the cardiovascular system by regulating the PI3K/Akt signaling pathway. 30,31) However, whether AS-IV further induces HO-1 expression by regulating the PI3K/Akt signaling pathway and its downstream effectors remains unclear.…”
Section: Discussionmentioning
confidence: 99%